CSR Reporting - Whether and How It Affects the Financial Results of Enterprises - Literature Review - Agnieszka JUDKOWIAK; Agnieszka MOSKAL (Communications of International Proceedings, 2021)
Corporate social responsibility is gaining more importance in economic life. Activities undertaken by enterprises, both large and small, for the benefit of the environment, local community or employees, more often constitute one of the components of the entire management process. The amount and quality of disclosed information on corporate social responsibility may affect the financial results of enterprises in various ways. The aim of the article is to determine, on the basis of the research conducted so far, whether the disclosure of information about CSR affects the financial results of enterprises. The study used the literature review method. The article consists of an introduction to the topic, a discussion of the essence of CSR, a presentation of the directions and scale of the impact of disclosing information about CSR in corporate reports on the achieved financial results and a summary. The results of the study show that disclosing information about CSR can have both a positive and negative impact on the results of enterprises' operations, measured by indicators such as: ROA, ROE.
Keywords: CSR; corporate social responsibility; CFP; corporate financial performance; literature review